IMMOBILIZATION OF α-AMYLASE ONTO K-10 MONTMORILLONITE: CHARACTERIZATION AND COMPARISON OF ACTIVITY IN A BATCH AND A FIXED-BED REACTOR - Sanjay G.; Sugunan S. (My University, 2005)
α-amylase was immobilized on acid-activated montmorillonite K-10 via adsorption and covalent linkage. The immobilized enzymes were characterized by X-ray diffraction (XRD), surface area measurements, 27Al nuclear magnetic resonance (NMR) and scanning electron microscopy (SEM). Surface area measurements indicate pore blockage due to linking of the enzyme in the vicinity of the pore mouth. The XRD demonstrates intercalation of enzyme upon immobilization. The NMR studies indicate that, during adsorption, tetrahedral Al sites are involved, while covalent binding occurs exclusively on the octahedral Al sites. The SEM images depict the changed morphology of the clay surface due to immobilization. The efficiency of immobilized enzymes for starch hydrolysis was tested in a batch and a fixed-bed reactor and the performances were compared. The immobilized α-amylase showed a broad pH profile and improved stability characteristics in both reactor types when compared to the free enzyme. The effectiveness factor increased in the fixed-bed reactor, implying that diffusional restrictions to mass transfer operate in the heterogeneous reaction and the use of a fixed-bed reactor leads to a reduction in these diffusional resistances. In the continuous run, 100% initial activity was maintained for 72 h, and after 96 h, >80% activity was retained. © 2005 The Mineralogical Society.
Keywords: α-AMYLASE; ADSORPTION; COVALENT BINDING; IMMOBILIZED ENZYMES; MONTMORILLONITE; STARCH HYDROLYSIS